Prevalence of Bilateral Impacted Mandibular Third Molars Undergoing Extraction. - KUMAR.S, DHINESH; PRABU, DINESH; RAMANATHAN, VISALAKSHI (The journal of contemporary issues in business and government, 2021)
The impacted tooth that is most frequently extracted is the mandibular third molar. The investigations for its removal include determining the type and degree of impaction so as to assess the level of difficulty during extraction. The aim of this study is to assess the prevalence of bilateral impacted mandibular third molars undergoing extraction. The materials and method includes a study sample of 500 patients who have undergone extractions of impacted mandibular third molars. Data analysis was done using SPSS PC Version 23.0(IBM;2016) software for statistics. Chi square test for independence between impacted mandibular third molar and gender. Chi square test which gives p value of 0.933 which is statistically significant denoting that there exists no association between gender and impacted mandibular third molar extraction among the study population. The prevalence of mandibular bilateral impacted third molar extraction is more common among males .